The application of the K-class system in mine seismicity - Wang, Chao; Zhan, Kai; Zhao, Xipo; Xu, Rui; Kong, Chao (Frontiers in Earth Science, 2024)
As seismology has evolved, scientists have developed various earthquake magnitude scales tailored for specific scenarios, including Richter magnitude (ML) for local, moderate quakes, moment magnitude (Mw) for large-scale seismic events, energy magnitude (Me), which correlates directly with the total energy released, and duration magnitude (MD) for quickly assessing shallow or nearby seismic activities. Despite these advances, these scales were not specifically designed to address the unique challenges posed by mine earthquakes, particularly in coal mine environments where seismic events are typically of lower energy and lower perceptibility but have potentially significant impacts. This study applies the K-class magnitude system for the first time to address significant discrepancies in magnitude values for the same seismic events in mine earthquakes, particularly in coal mines when different formulas are used. However, because current seismic monitoring systems in domestic coal mines continue to employ a variety of magnitude scales, we have developed a corrected Richter scale (MLc) specifically tailored to the geological conditions of coal mines. This adaptation facilitates the conversion to and from the K class, enhancing the accuracy and relevance of seismic assessments in these environments. Therefore, we conducted continuous blasting experiments at the Dongtan Coal Mine and derived the corrected Richter magnitude MLc. Based on data analysis, we fitted the energy attenuation coefficient and compared the K values with four types of traditional magnitude results. Finally, we derived the conversion relationship between the K class and the corrected Richter magnitude MLc, establishing a mine earthquake measurement system. The successful application of the K class in coal mines suggests its potential to be extended to the entire field of induced microseismicity, including mining-induced microseismicity, shale gas extraction-induced microseismicity, and oil extraction-induced microseismicity, providing valuable insights and tools for a broader range of geophysical research and industry practices.